2013
DOI: 10.1590/s1517-83822013000200026
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of agr groups and virulence genes among subclinical and clinical mastitis Staphylococcus aureus isolates from sheep flocks of the Northeast of Brazil

Abstract: Staphylococcus aureus is one of the most frequent mastitis causative agents in small ruminants. The expression of most virulence genes of S. aureus is controlled by an accessory gene regulator (agr) locus. This study aimed to ascertain the prevalence of the different agr groups and to evaluate the occurrence of encoding genes for cytotoxin, adhesins and toxins with superantigen activity in S. aureus isolates from milk of ewes with clinical and subclinical mastitis in sheep flocks raised for meat production The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 33 publications
0
18
0
3
Order By: Relevance
“…The primers and amplification conditions of these genes were previously described by Darwish et al ( icaA , icaD ) [ 21 ], Otsuka et al ( fnbpA ) [ 22 ], Tristan et al ( fnbpB , clfA , clfB , cna , bbp ) [ 23 ], Campbell et al ( ebpS , sdrC , sdrD ) [ 24 ], and Peacock et al ( sdrE ) [ 25 ]. N315 was used as positive control for icaA , icaD, ebpS, sdrC,sdrD, and sdrE ; RN4220 was used as positive control for fnbpA , fnbpB , clfA , clfB ; ATCC25923 was used as positive control for cna and bbp [ 26 , 27 ]. The presence and size of the PCR products were confirmed by electrophoresis on 1.5% agarose gels.…”
Section: Methodsmentioning
confidence: 99%
“…The primers and amplification conditions of these genes were previously described by Darwish et al ( icaA , icaD ) [ 21 ], Otsuka et al ( fnbpA ) [ 22 ], Tristan et al ( fnbpB , clfA , clfB , cna , bbp ) [ 23 ], Campbell et al ( ebpS , sdrC , sdrD ) [ 24 ], and Peacock et al ( sdrE ) [ 25 ]. N315 was used as positive control for icaA , icaD, ebpS, sdrC,sdrD, and sdrE ; RN4220 was used as positive control for fnbpA , fnbpB , clfA , clfB ; ATCC25923 was used as positive control for cna and bbp [ 26 , 27 ]. The presence and size of the PCR products were confirmed by electrophoresis on 1.5% agarose gels.…”
Section: Methodsmentioning
confidence: 99%
“…The prevelance of lukD-lukE was variable in literatures where in a study performed in USA, it was 36.5% (Abdalrahman and Fakhr, 2015). In another study, 82.8%, of isolates were lukD-lukE positive (de Almeida et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…Although, these isolates were obtained from samples with negative results in California mastitis test, and they could be considered healthy, or with no indication of subclinical infection, this fact can contribute to the persistence of infection of subclinical staphylococcal infection in animals. Almeida et al (2013) suggested that the presence of clfA gene, a receptor for fibronectin, is involved in the colonization of the mammary gland epithelium despite the clinical picture of the mastitis. In this study, S. aureus samples isolated from milkers' hands were positive for clfA, clfB and hla genes, and may be a key factor for the maintenance of these virulence factors in these agents causing disease to both human and buffalo.…”
Section: Characterization Of Virulence Related Genesmentioning
confidence: 99%